Advances in impedance based fault location in distribution systems - Aboshady, Fathy (2019)
The transmission and distribution system is seeing an increasing penetration of embedded generation especially renewable energy sources (RES) and its resilience will be further challenged by the increasing electrification of transport and heating/air conditioning. Renewable energy sources behave differently to conventional generation systems from both a power system protection and an operation point of view. For this reason, embedding renewable energy sources and its effect on the protection of the electricity system requires more investigation.